Pengaruh Kepemimpinan, Kompensasi, Dan Disiplin Kerja, Terhadap Kinerja Karyawan Bagian Produksi PT. Langgeng Jaya Plastindo Gresik - Pristianto, Firdian Agung; Hidayati, Roziana Ainul (Jurnal Mahasiswa Manajemen, 2024)
Background - Performance can be achieved if the company has good human resources and has high performance, but the performance of employees within an organization or company does not always increase, sometimes the performance of employees in the company also decreases. Employee performance will be very important for PT. Langgeng Jaya Plastindo which relies on the active role of all its Human Resources to improve employee performance. Aim - This study aims to determine the partial effect of leadership, compensation and work discipline on the performance of employees in the production division of PT Langgeng Jaya Plastindo Gresik. Design / Methodology / Approach - This study uses a quantitative method approach. The population in this study, namely PT. Langgeng Jaya Plastindo Gresik. The sample in this study used the Isaac and Michae sample method with a significance level of 5% from a total population of 140, so the sample taken was 100 employees. Data collection techniques using primary data and informant data collection using questionnaires or questionnaire surveys using data instrument tests, classical assumption tests, multiple linear regression analysis and hypothesis testing (t test and coefficient of determination) with the help of SPSS program. Findings - The results of this study indicate that the variables of Leadership (X1), Compensation (X2) and Work Discipline (X3) each partially have a significant effect on employee performance (Y) the Adjusted R square value of 0.609. This shows that 60.9% of the variation in employee performance variables can be explained by leadership, compensation and work discipline, while the remaining 39.1% can be explained by other factors outside of this study. Research Implication – The results of this study are expected to be input and as additional information for the company in leadership, compensation, and work discipline on employee performance at PT Langgeng Jaya Plastindo. Limitations - The limitation of this study is that it only uses three variables while there are many other factors that can affect employee performance related to the findings of phenomena that may occur in the company.